Trade effects of standards harmonization in the EU: Improved access for non-EU partners - Anirudh Shingal; Malte Ehrich (Indian Council for Research on International Economic Relations (ICRIER), 2019)
In September 2008, the EU replaced national-level regulation on Maximum Residue Levels (MRLs) in pesticides with harmonized Community-wide regulation. Using data on pesticide MRLs for 53 trading partners over 2005-2014, we examine the effects of this harmonization on both intra- and extra-EU imports in an original empirical contribution to this literature. We also embed regulatory heterogeneity in the Melitz (2003) framework in a theoretical contribution. We find robust evidence for adverse effects of regulatory heterogeneity on intra-EU trade in the pre-harmonization period, which questions the implementation of the Cassis de Dijon principle. Our findings also suggest that the EU's MRL harmonization may have improved access for non-EU, including non-OECD, exporters to the Common Market.
Keywords: F13; F14; I18; 330; Standards; MRL Regulation; Harmonization; EU; Trade